Analisis Kohesi Leksikal dan Gramatikal pada Novel Sepasang Angsa Putih untuk Palupi karya Marliana Kuswanti - Mutiara Dewi, Mona; Sabardila, Atiqa (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this research is to find out the forms of lexical cohesion and grammatical cohesion contained in the novel entitled A Pair of White Swans for Palupi by Marliana Kuswanti. The type of research used in this research is qualitative research. The data analysis method used in this research is the matching and agih method. The advanced technique used is the determination sorting technique (PUP). The basic technique used in this method is the direct element technique (BUL). The results of the analysis are presented in the form of information, namely by presenting the data through an explanation or descriptive. The data obtained on lexical cohesion are repetition (repetition), synonymy (word matching), collocation (word pairing), hyponymy (up-down relationship), antonymy (opposite word), and equivalence (equivalence). Then for grammatical cohesion there are references or references, substitutions or substitutions, ellipsis or omissions, and conjunctions or connectors.